Pengaruh Pola Asuh Orang Tua dan Fasilitas Laboratorium Komputer terhadap Hasil Belajar Siswa SMA Negeri 3 Kubu - Safitri, Nelly; Yuvensius, Yuvensius; Zulkarnain, Eko (PT The Collaboration UVW, 2023)
This study aims to determine parenting styles and computer laboratory facilities on student learning outcomes at SMA Negeri 3 Kubu. There are two variables in this study, namely, the independent variables include parenting parents and computer laboratory facilities, while the related variables are learning outcomes. In this study, the researcher used a quantitative descriptive research method. The form of research that is considered suitable and in accordance with the method required in this research is the ex post facto research form. The population in this study were all students of class X and XI SMA Negeri 3 Kubu. proportional random sampling technique. Proportional aims so that each class can be represented in proportion and carried out randomly, namely collecting samples randomly. The data collection technique uses a questionnaire or questionnaire technique, before being used the data collection tool has been validated and tested for reliability. Data analysis techniques from the results of this study are simple regression analysis and multiple linear regression. The results that are known after conducting this research are that there is an influence of parenting styles on the learning outcomes of SMA Negeri 3 Kubu students. There is an influence of computer laboratory facilities on student learning outcomes of SMA Negeri 3 Kubu. There is an influence of parents' upbringing and computer laboratory facilities together on the learning outcomes of SMA Negeri 3 Kubu students.